Penerapan Aplikasi Sistem Informasi Social Network Sebagai Media Komunikasi Dan Promosi Pada SMP Muhammadiyah Salatiga - Kustiyono (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
SMP Muhammadiyah Salatiga designing a Website which is also integrated with social networking is equipped with several facilities, such as school bulletin board, news, articles, schedule of events, photo gallery, downloadable content and web forums to provide convenience to members for sharing online. This study was developed using the method of system development Research and Developmnet [1] which consists of: Research and Information Collection, Planning, Develop Preliminary Form of Product, Preliminary Field Testing, Product Revision Main, Main Field Testing, Operational Product Revision, Operational, Field Testing, Final Product Revision, Dissemination and Implementation using the programming language PHP with MySQL database. The results showed that the system serves as a medium of information kominukasi with students, teachers, employees, alumni and the community as well as a media campaign.